Resource allocation for device to device communication in future mobile network (5G and beyond) - Haroune AHTIRIB (Universty Of El-oued جامعة الوادي, 2025)
The number of mobile users has increased at an unprecedented rate over the past ten years, overwhelming the cellular network core. Numerous technologies are being researched to advance to the next generation of cellular networks, dubbed "the fifth generation" (5G) and 5G beyond, in order to keep up with this expansion of cellular networks. One of those technologies claims to increase throughput overall, minimize latency, enhance spectral and energy efficiency, and offload the network core. The Device-to-Device (D2D) communication technology has claimed all of those claims. Direct connection between devices (D2D communication) excludes the Base Station (BS). D2D communication technology has numerous obstacles in achieving its goals. Throughput is maximized and interference is reduced when resources are allocated and power is controlled effectively. Within the context of 5G cellular networks, we study the joint power and resource allocation problem for D2D communication in this thesis. In this theses, we primarily utilize wireless channel data that exhibits slowly shifting large-scale fading to conduct spectrum sharing and power allocation. The overall ergodic capacity of all cellular user equipment (CUE) links is initially considered as the optimization target in order to maximize the overall throughput of CUE links while ensuring the reliability of each D2D link. Then, the expansion of the minimum ergodic capacity is measured to ensure a more consistent capacity performance across all CUE links. We utilized algorithms that are resilient to channel fluctuations and produce optimal resource allocation. ان زيادة عدد مستخدمي الهاتف المحمول بمعدل غير مسبوق على مدى السنوات العشر الماضية، أدى إلى زيادة العبء على الشبكة الخلوية الأساسية. حيث هذا الاخير حث الباحثين على البحث في العديد من التقنيات للتقدم إلى الجيل القادم من الشبكات الخلوية، والتي يطلق عليها اسم "الجيل الخامس"5G و ما بعده، وذلك لمواكبة هذا التوسع في الشبكات الخلوية. و من احد اهم هذه التقنيات هي الاتصال من جهاز الى جهاز (D2D),حيث انها تعمل على زيادة الإنتاجية بشكل عام و تقليل زمن الوصول، وتعزيز الكفاءة الطيفية والطاقة، وتخفيف عبء الشبكة. تواجه تكنولوجيا الاتصالات D2D العديد من العقبات في تحقيق أهدافها. يتم تعظيم الإنتاجية وتقليل التداخل عندما يتم تخصيص الموارد والتحكم في الطاقة بشكل فعال. في سياق الشبكات الخلوية G5، قمنا بدراسة مشكلة تخصيص الطاقة والموارد المشتركة للاتصالات D2D في هذه الأطروحة. في هذه الأطروحة، نستخدم في المقام الأول بيانات القناة اللاسلكية التي تظهر تحولًا بطيئًا في الخبو واسع النطاق لإجراء تقاسم الطيف وتخصيص الطاقة. تعتبر السعة المريحة الإجمالية لجميع وصلات أجهزة المستخدم الخلوية (CUE) في البداية بمثابة هدف التحسين من أجل زيادة الإنتاجية الإجمالية لروابط CUE إلى أقصى حد مع ضمان موثوقية كل رابط D2D. بعد ذلك، يتم قياس توسيع الحد الأدنى من السعة المريحة لضمان أداء أكثر اتساقًا للسعة عبر جميع وصلات CUE. لقد استخدمنا خوارزميات تتسم بالمرونة في التعامل مع التقلبات وإنتاج التخصيص الأمثل للموارد.
أطروحة دكتوراه تخصص شبكات و إتصال في العلوم التكنولوجيا
Keywords: Cellular networks; Device-to-device communication; Ergodic capacity; Power; allocation; Resource allocation.; الشبكات الخلوية، الاتصالات من جهاز إلى جهاز، السعة الارجودية، تخصيص الطاقة، تخصيص الموارد.